Tracheal Duplication Cyst Coexisting with Tracheoesophageal Fistula in a Neonate – An Intraoperative Surprise - Shrilakshmi Aithal; Avinash Jadhav; Shubhalaxmi Nayak; Manish Pathak; Arvind Sinha (Journal of Indian Association of Pediatric Surgeons)
Duplication of the trachea is a rare anomaly, with few reported cases. This report presents a neonate with tracheoesophageal fistula (TEF), where tracheal duplication was incidentally discovered during repair. It is an effort to discuss the rare congenital anomaly and management options when faced with such surprises intraoperatively.